Optimization models in the SCM-system: progressive supply chain management - Lukina, S. G.; Sadykov, A. A.; Fayzullin, R. V. (Вестник университета, 2023)
Transformations in socio-economic space affect functioning of entrepreneurial activity, leading to a change in the configuration of business processes. In the context of increasing complexity of external environment and digitalization, subjects must ensure the activities effectiveness based on supply chains optimization. Entities are required to use progressive methods of supply chain management. The purpose of the study is to analyze main optimization models in supply chain management (SCM) to determine progressive ways to improve them. The issues of SCM have been worked out, models of their optimization considered and suggestions for their improvement made. Theoretical analysis and generalization of information that allow to substantiate the SCM optimization models’ apparatus (SCOR, DCOR, CCOR) act as a methodological basis. As a result, it is proposed to focus on possibilities of progressive supply chain management, which make it possible to use information technologies to work through a large array of data and continuously obtain values for indicators, contributing to the development of models for optimizing logistics operations and processes in the SCM. The developments obtained are planned to be used for the development of practical models for optimizing enterprises’ supply chains.